2013
DOI: 10.1603/ec13004
|View full text |Cite
|
Sign up to set email alerts
|

A Repellent Net as a New Technology to Protect Cabbage Crops

Abstract: Floating row covers or insect-proof nets with fine mesh are effective at protecting vegetable crops against aphids but negatively impact plant health, especially under warm conditions. Furthermore, in control of cabbage insect pests, aphid parasitoids cannot enter the fine-mesh nets, leading to frequent aphid outbreaks. To surmount these difficulties, a 40-mesh-size repellent net treated with alphacypermethrin was studied in laboratory and field tests. Results showed both irritant and repellent effects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
(44 reference statements)
2
16
0
Order By: Relevance
“…These products (geraniol and citronellol) could be used in insect-proof net treatment, and this strategy has already shown good results in the field with chemical products. For example, Martin et al 19,52 showed that a net treated with alpha-cypermethrin blocked the pest Myzus persicae on cabbage crops in field conditions because of the irritant and repellent effects of this chemical. Moreover, a net treated with alpha-cypermethrin was shown to reduce the whitefly net-crossing rate and improve tomato crop protection as compared with untreated netting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These products (geraniol and citronellol) could be used in insect-proof net treatment, and this strategy has already shown good results in the field with chemical products. For example, Martin et al 19,52 showed that a net treated with alpha-cypermethrin blocked the pest Myzus persicae on cabbage crops in field conditions because of the irritant and repellent effects of this chemical. Moreover, a net treated with alpha-cypermethrin was shown to reduce the whitefly net-crossing rate and improve tomato crop protection as compared with untreated netting.…”
Section: Discussionmentioning
confidence: 99%
“…One way to protect plants from pest insects without using pesticides is to create a visual and physical barrier between the insect and the plant with a net . In Beninese fields, insect‐proof nets (IPNs) have been shown to provide more effective protection against the diamondback moth ( Plutella xylostella ) and other Lepidoptera species than foliar insecticide sprays . However, in tropical regions with high temperature and humidity levels, the use of fine mesh nets increases the risk of plant pathogen development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the five management practices, no hole was found in tomato fruits because no insect could enter into the fruit. In fact, the net with finest pore diameter made a strong physical barrier to pests that literally disrupted their feeding on tomato fruits (Martin et al 2013), resulting in no hole on tomato. Side by side, other three ecofriendly management tools also effectively decreased the fruit damage by the pest but their efficacy against fruit damage was not statistically different ( Fig.…”
Section: Effect Of Different Management Practices On the Holes Of Infmentioning
confidence: 99%
“…Preliminarily assessments of yield using EFNs suggest that yield over four years (for a plot of 12m 2 ) might be as high as FCFA 172,800 or € 263 (FCFA 21,600 or € 33 per cycle), which would be almost double the yield of farmers' current practices. Further field experiments are currently being undertaken (see Martin et al, 2013) but if these preliminary results are verified, this would mean that farmer's concern about the two-fold labor requirements for EFNs (two instead of one person) can be allayed by a doubling of yield depending of the climate conditions (Muleke et al, 2013(Muleke et al, , 2014. It could also be that the research project itself had an overall positive impact of farmer's understanding of vegetable production and proper use of pesticides through the participation in the EFNs on-farm trials.…”
Section: Discussionmentioning
confidence: 99%